Acanthosis nigricans in the knuckles: An early, accessible, straightforward, and sensitive clinical tool to predict insulin resistance. Issue 1 (1st January 2018) - González-Saldivar, Gloria; Rodríguez-Gutiérrez, René; Treviño-Alvarez, Andrés Marcelo; Gómez-Flores, Minerva; Montes-Villarreal, Juan; Álvarez-Villalobos, Neri Alejandro; Elizondo-Plazas, Anasofía; Salcido-Montenegro, Alejandro; Ocampo-Candiani, Jorge; González-González, José Gerardo
ABSTRACT: Any clinical/biochemical marker revealing obesity or diabetes before their appearance is valuable. Insulin resistance (IR) is present in both disorders many years before occurrence. Accordingly, we determined whether acanthosis nigricans (AN) in the knuckles is associated to higher insulin and homeostasis model assessment for estimated insulin resistance (HOMA-IR) index values, and assessed the influence of body-mass index (BMI) and the diagnostic performance of AN in the knuckles to detect IR. In this cross-sectional controlled study, we included men or women, 18 to 23 years old, with or without AN in the knuckles. In 149 cases with AN in the knuckles and 145 controls, fasting insulin was higher in cases (13.45 µU/mL ± 7.8 vs. 8.59 µU/mL ± 3.63, P < .001, respectively). Mean HOMA-IR index was also higher (2.86 ± 1.68 vs. 1.78 ± 0.77, P < .001). A significant increase in fasting insulin and HOMA-IR values between and within BMI groups from normal through obese category was identified in controls and cases. By multivariate regression analysis, cases with normal BMI were significantly associated to a HOMA-IR ≥2.5 (OR = 3.09, CI95% = 1.75–5.48, P = .001). A model of AN in the knuckles, normal BMI, and increased waist circumference allowed identifying 2 out of 3 cases with HOMA-IR index ≥2.5. AN in the knuckles could be addressed with two aims: as an easy, accessible, and costless diagnostic tool suggesting hyperinsulinemia secondary to IR, and, an early marker of IR even in the absence of overweight or obesity.